2021
DOI: 10.32466/eufv-cyh.2021.17.645.349-361
|View full text |Cite
|
Sign up to set email alerts
|

Barreras y oportunidades para la comunicación de la responsabilidad social en redes sociales

Abstract: El objetivo del artículo es realizar una revisión de la literatura sobre las barreras y oportunidades de la comunicación en redes sociales de los contenidos vinculados con la Responsabilidad Social Corporativa (RSC) y la gestión de la sostenibilidad. Para ello, se han seleccionado 466 artículos de Web of Science con palabras clave relacionadas con el objetivo. Para el análisis, solo se han tenido en cuenta aquellas publicaciones en revistas científicas y escritas en inglés. El número total de artículos analiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In a recent study on barriers and opportunities for communicating a key intangible of corporate communication such as CSR it was shown that the topic of the contents related to intangible management should be considered in order to evaluate its capacity to connect with Rangel-Pérez, C., Monfort, A. & Miquel, S. Thematic dis/connection of Ibex35 companies to generate dialogue with their stakeholders via Twitter during the pandemic stakeholders (Monfort & Mas-Iglesias, 2021). Thus, literature has shown that to increase interaction with individuals, topics related to ethics or legal compliance content must be addressed (Wang & Pala, 2020) or those related to business and financial performance (Monfort et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…In a recent study on barriers and opportunities for communicating a key intangible of corporate communication such as CSR it was shown that the topic of the contents related to intangible management should be considered in order to evaluate its capacity to connect with Rangel-Pérez, C., Monfort, A. & Miquel, S. Thematic dis/connection of Ibex35 companies to generate dialogue with their stakeholders via Twitter during the pandemic stakeholders (Monfort & Mas-Iglesias, 2021). Thus, literature has shown that to increase interaction with individuals, topics related to ethics or legal compliance content must be addressed (Wang & Pala, 2020) or those related to business and financial performance (Monfort et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Unsurprisingly, sustainability reports have gained considerable traction in the corporate world, likely because they are voluntary and subject to organizational guidelines (Acevedo & Piñero, 2019;Buitrago, 2021;Her-rera et al, 2013;Hurtado-Jaramillo et al, 2016;Monfort & Mas, 2021;Semenova, 2023;Thijssens et al, 2016). While these reports are certainly a key communications tactic, they are neither the only nor the most important tactic available.…”
Section: Introductionmentioning
confidence: 99%